Science in a Bottle - Marke, Sandra; Nang Chan Yeema (New York. USA Scholastic Book Services, 1995)
Can you pick up a bottle without touching it? Can you make a fountain in a bottle? Can you raise a bottle full of sea monkeys?
Keywords: Juvenile Nonfiction